Anti-crack synchronous chip seal structure
By adopting a crack-resistant synchronous gravel seal structure in the semi-rigid base asphalt pavement, the combination of modified asphalt, fiber and recycled material layers is used to form a dense structure, which solves the problem of insufficient waterproof and crack resistance and extends the road surface lifespan and reduce costs.
Patent Information
- Application Number
- CN202420761203.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Utility models(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-12
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2034-04-12
AI Technical Summary
The existing semi-rigid base layer asphalt pavement has poor waterproof and crack resistance, resulting in crack-proof and water damage on the road surface, shortening service life.
Adopt a crack-resistant synchronous gravel seal structure, including a modified emulsified asphalt first bonding layer, a glass or basalt fiber layer, a recycled fine material layer, a slow crack non-stick wheel emulsified asphalt second bonding layer and a recycled coarse material The layer forms a dense structure through the misaligned fiber arrangement and the envelopment of aggregates of different particle sizes, enhancing bonding and waterproofing properties.
Effectively inhibit reflective cracks, prevent rainwater from seeping, enhance tensile strength and fatigue resistance, extend the service life of semi-rigid base asphalt pavement, and reduce the cost of engineering, with low carbon and environmental protection characteristics.
Smart Images

Figure CN222182950U_ABST
Abstract
Description
[0001] manual Technical Field
[0002] The utility model belongs to the technical field of road engineering, and relates to a synchronous crushed stone seal structure, in particular to an anti-cracking synchronous crushed stone seal structure, which has dual functions of waterproofing and anti-cracking, and is mainly used as a functional layer between a semi-rigid base layer and an asphalt concrete surface layer. Technical Background
[0003] In the past two decades, with the rapid development of my country's transportation industry, the layout of the road network has gradually improved, and the technical level and overall quality of the road surface have been significantly improved, which has strongly supported the sustained and rapid development of society and economy. But at the same time, the high-speed and heavy-loaded road transportation has brought severe challenges to the construction and operation of road infrastructure. At present, the common structural layers of my country's highway asphalt pavement are the base layer and the asphalt surface layer. The asphalt surface layer is usually paved in three layers: lower, middle and upper. The base layer usually adopts a semi-rigid cement-stabilized gravel design. Since the semi-rigid base layer and the asphalt surface layer are materials of different properties, the key to this type of pavement is to ensure good adhesion and continuity between the two. In addition, when the asphalt surface layer seeps water, it will mostly concentrate on the junction of the surface layer and the base layer, causing the asphalt pavement to be pumped, loose, and potholes. Between the asphalt surface layer and the base layer, a functional layer of the lower seal layer is widely added, which mainly plays a waterproof and bonding role, increases the bonding force between the asphalt surface layer and the base layer, prevents water from the road surface from entering the base layer, and prevents water damage between layers.
[0004] At present, the semi-rigid base asphalt pavement of my country's highways generally adopts emulsified asphalt synchronous macadam seal, slurry seal, modified asphalt synchronous macadam seal, rubber asphalt synchronous macadam seal and other technologies as the lower seal, but their crack resistance and waterproof performance have not achieved the ideal effect. Since the traditional synchronous macadam seal and slurry seal do not have the ability to resist cracks, when cracks appear in the semi-rigid base of cement-stabilized macadam, they will soon show up, and in some projects, they even have a negative effect on the interlayer bonding.
[0005] Although the causes and forms of cracks in asphalt pavements are varied, for asphalt pavements on highways in southern my country, the main causes of asphalt pavement cracks are structural cracks in the semi-rigid base caused by vehicle loads and reflection cracks caused by cracks generated by base shrinkage reflecting upward. Since semi-rigid base asphalt pavements will inevitably crack, surface water will penetrate into the asphalt layer and even the semi-rigid base through these cracks (cracks) during the rainy season in the south, greatly reducing its strength and causing early damage to the asphalt pavement. This is also one of the many reasons why the service life of semi-rigid base asphalt pavements on highways in my country does not reach the designed life.
[0006] Therefore, in view of the problems that the traditional lower sealing layer of semi-rigid base asphalt pavement in southern my country has unsatisfactory waterproof and crack resistance, it is very necessary to propose a new type of lower sealing layer of semi-rigid base asphalt pavement, so that it can achieve the purposes of simulating the appearance of reflective cracks, strengthening the waterproof function, ensuring the interlayer adhesion, and extending the service life of the semi-rigid base asphalt pavement. Utility Model Content
[0007] The purpose of the utility model is to develop a crack-resistant synchronous crushed stone seal structure in view of the various defects existing in the seal layer under the above-mentioned semi-rigid base asphalt pavement. The structure can effectively suppress the appearance of reflective cracks in the semi-rigid base asphalt pavement, prevent rainwater from seeping in, and extend the service life of the semi-rigid base asphalt pavement. It has the characteristics of low cost, simple process, low carbon and environmental protection, and fast construction speed.
[0008] In order to achieve the above purpose, the utility model adopts the following technical solutions:
[0009] A crack-resistant synchronous crushed stone sealing layer structure comprises, from bottom to top, a first bonding layer, a fiber layer, a recycled fine material layer, a second bonding layer, and a recycled coarse material layer laid on a semi-rigid base layer.
[0010] Furthermore, the asphalt of the first bonding layer is one of modified emulsified asphalt, polymer modified asphalt and rubber asphalt, and the asphalt usage of the first bonding layer is 1.0 kg / m 2 -2.0kg / m 2 ;
[0011] Furthermore, the asphalt technical indicators of the first bonding layer meet the requirements of the "Technical Specifications for Highway Asphalt Pavement Construction";
[0012] Furthermore, the fibers of the fiber layer are one of glass fiber chopped strands and basalt fiber chopped strands;
[0013] Furthermore, the amount of chopped fibers in the fiber layer is 0.3 kg / m 2 -0.5Kg / m 2 ;
[0014] Furthermore, the length of the chopped strands of the fiber layer is 1 cm to 4 cm;
[0015] Furthermore, the chopped strands of the fiber layer are evenly spread on the first bonding layer, and the chopped strands are arranged in a disordered manner;
[0016] Furthermore, the fine aggregate used in the recycled fine material layer is fine aggregate obtained by processing RAP old asphalt pavement milling material, and the particle size of the fine aggregate is 0-2.36 mm;
[0017] Furthermore, the old asphalt content of the finely divided aggregate is not less than 10%;
[0018] Furthermore, the amount of fine aggregate used in the recycled fine material layer is 6 kg / m 2 -15Kg / m 2 ;
[0019] Furthermore, the asphalt of the second bonding layer is a slow-cracking non-stick wheel emulsified asphalt, and the usage amount of the slow-cracking non-stick wheel emulsified asphalt is 0.4 kg / m 2 -1.0kg / m 2 ;
[0020] Furthermore, the evaporation residue content of the slow-cracking non-stick wheel emulsified asphalt is 40%-55%, the softening point of the evaporation residue is not less than 75°C, and it does not stick to the vehicle tire when the air temperature reaches 60°C;
[0021] Furthermore, the coarse aggregate used in the recycled coarse material layer is finely divided coarse aggregate processed from RAP old asphalt pavement milling material, and the particle size of the finely divided coarse aggregate is one of 2.36-4.75mm, 4.75-9.5mm, and 9.5-13.2mm;
[0022] Furthermore, the old asphalt content of the finely divided coarse aggregate is not more than 3%;
[0023] Furthermore, the amount of finely divided coarse aggregate in the recycled coarse material layer is 60%-75% of the full paving rate.
[0024] Compared with the prior art, the utility model has the following advantages:
[0025] 1. The first bonding layer forms a dense asphalt layer on the surface of the semi-rigid base layer. On the one hand, it can prevent the moisture in the gaps of the upper asphalt pavement from seeping into the base layer, causing water damage to the base layer; on the other hand, it can effectively block the tiny gaps on the surface of the semi-rigid base layer, preventing the capillary water in the base layer from entering the upper asphalt pavement, causing water damage to the asphalt pavement.
[0026] 2. The fibers are randomly arranged at the bottom of the synchronous crushed stone seal layer, which can effectively absorb, diffuse and redistribute the local concentrated stress in the pavement structure, effectively reduce the stress in the pavement structure, reduce the generation of cracks in the pavement structure layer, and inhibit and prevent the appearance of reflective cracks, increasing the tensile strength and fatigue resistance by more than 30%.
[0027] 3. The fine aggregate used in the recycled fine material layer has a small particle size and a large content of old asphalt. When combined with the first bonding layer and compacted by a roller, a dense high-asphalt content structural layer of about 1 cm is formed between the semi-rigid base and the upper asphalt mixture. This layer has super flexibility, viscoelastic properties and impermeability, and can disperse and control the local concentrated stress generated in the base layer.
[0028] 4. The recycled coarse material layer and the recycled fine material layer have different particle sizes, which are embedded and filled with each other, making the waterproof bonding layer more compact and less susceptible to damage by asphalt mixture construction equipment.
[0029] 5. The refined material obtained by processing RAP old asphalt pavement milling material has a certain amount of old asphalt remaining on the surface, which makes the bonding effect between the refined material and the first bonding layer and the second bonding layer much higher than the adhesion between the fresh aggregate and the bonding layer.
[0030] 6. The aggregates used for the synchronous crushed stone seal are all derived from RAP old asphalt pavement milling materials, which can greatly reduce the project cost and has a demonstration effect of green, low-carbon and recycling of waste resources. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 The utility model is a schematic diagram of a crack-resistant synchronous crushed stone seal structure.
[0032] In the figure: 1. semi-rigid base layer; 2. first bonding layer; 3. fiber layer; 4. recycled fine material layer; 5. second bonding layer; 6. recycled coarse material layer. DETAILED DESCRIPTION
[0033] The following is combined with Figure 1 And specific embodiments are provided to further illustrate the utility model.
[0034] Example 1
[0035] A crack-resistant synchronous crushed stone seal structure comprises, from bottom to top, a first bonding layer (2) laid on a semi-rigid base layer (1), a fiber layer (3), a recycled fine material layer (4), a second bonding layer (5), and a recycled coarse material layer (6).
[0036] Furthermore, the asphalt of the first bonding layer (2) is modified emulsified asphalt, and the asphalt usage of the first bonding layer (2) is 1.0 kg / m 2 ;
[0037] Furthermore, the technical indexes of the modified emulsified asphalt of the first bonding layer (2) meet the requirements of the Technical Specifications for Highway Asphalt Pavement Construction;
[0038] Furthermore, the fibers of the fiber layer (3) are chopped basalt fibers;
[0039] Furthermore, the amount of chopped fibers in the fiber layer (3) is 0.5 kg / m 2 ;
[0040] Furthermore, the length of the short shreds of the fiber layer (3) is 4 cm;
[0041] Furthermore, the chopped strands of the fiber layer (3) are evenly spread on the first adhesive layer (2), and the chopped strands are arranged in a disordered manner;
[0042] Furthermore, the fine aggregate used in the recycled fine material layer (4) is fine aggregate obtained by processing RAP old asphalt pavement milling material, and the particle size of the fine aggregate is 0-2.36 mm;
[0043] Furthermore, the old asphalt content of the finely divided aggregate is 12%;
[0044] Furthermore, the amount of finely divided aggregate in the recycled fine material layer (4) is 6 kg / m 2 ;
[0045] Furthermore, the asphalt of the second adhesive layer (5) is a slow-cracking non-stick wheel emulsified asphalt, and the usage amount of the slow-cracking non-stick wheel emulsified asphalt is 1.0 kg / m 2 ;
[0046] Furthermore, the evaporation residue content of the slow-cracking non-stick wheel emulsified asphalt is 40%, the softening point of the evaporation residue is 76°C, and it does not stick to the vehicle tire when the air temperature reaches 60°C;
[0047] Furthermore, the coarse aggregate used in the recycled coarse aggregate layer (6) is finely divided coarse aggregate processed from RAP old asphalt pavement milling material, and the particle size of the finely divided coarse aggregate is 2.36-4.75 mm;
[0048] Furthermore, the old asphalt content of the finely divided coarse aggregate is 2.3%;
[0049] Furthermore, the amount of finely divided coarse aggregate in the recycled coarse material layer (6) is 75% of the full paving rate.
[0050] Example 2
[0051] A crack-resistant synchronous crushed stone seal structure comprises, from bottom to top, a first bonding layer (2) laid on a semi-rigid base layer (1), a fiber layer (3), a recycled fine material layer (4), a second bonding layer (5), and a recycled coarse material layer (6).
[0052] Furthermore, the asphalt of the first bonding layer (2) is rubber asphalt, and the asphalt usage of the first bonding layer (2) is 2.0 kg / m 2 ;
[0053] Furthermore, the asphalt technical index of the first bonding layer (2) meets the requirements of the "Technical Specifications for Highway Asphalt Pavement Construction";
[0054] Furthermore, the fibers of the fiber layer (3) are chopped glass fibers;
[0055] Furthermore, the amount of chopped fibers in the fiber layer (3) is 0.42 kg / m 2 ;
[0056] Furthermore, the length of the chopped strands of the fiber layer (3) is 1 cm;
[0057] Furthermore, the chopped strands of the fiber layer (3) are evenly spread on the first adhesive layer (2), and the chopped strands are arranged in a disordered manner;
[0058] Furthermore, the fine aggregate used in the recycled fine material layer (4) is fine aggregate obtained by processing RAP old asphalt pavement milling material, and the particle size of the fine aggregate is 0-2.36 mm;
[0059] Furthermore, the old asphalt content of the finely divided aggregate is not less than 10.2%;
[0060] Furthermore, the amount of fine aggregate in the recycled fine material layer (4) is 15 kg / m 2 ;
[0061] Furthermore, the asphalt of the second bonding layer (5) is a slow-cracking non-stick wheel emulsified asphalt, and the usage amount of the slow-cracking non-stick wheel emulsified asphalt is 0.9 kg / m 2 ;
[0062] Furthermore, the evaporation residue content of the slow-cracking non-stick wheel emulsified asphalt is 55%, the softening point of the evaporation residue is 80°C, and it does not stick to the vehicle tire when the air temperature reaches 60°C;
[0063] Furthermore, the coarse aggregate used in the recycled coarse aggregate layer (6) is finely divided coarse aggregate processed from RAP old asphalt pavement milling material, and the particle size of the finely divided coarse aggregate is 9.5-13.2 mm;
[0064] Furthermore, the old asphalt content of the finely divided coarse aggregate is 1%;
[0065] Furthermore, the amount of refined coarse aggregate in the recycled coarse material layer is 60% of the full paving rate.
[0066] Example 3
[0067] A crack-resistant synchronous crushed stone seal structure comprises, from bottom to top, a first bonding layer (2) laid on a semi-rigid base layer (1), a fiber layer (3), a recycled fine material layer (4), a second bonding layer (5), and a recycled coarse material layer (6).
[0068] Furthermore, the asphalt of the first bonding layer (2) is polymer modified asphalt, and the amount of asphalt used in the first bonding layer (2) is 1.5 kg / m 2 ;
[0069] Furthermore, the asphalt technical index of the first bonding layer (2) meets the requirements of the "Technical Specifications for Highway Asphalt Pavement Construction";
[0070] Furthermore, the fibers of the fiber layer (3) are chopped glass fibers;
[0071] Furthermore, the amount of chopped fibers in the fiber layer (3) is 0.3 kg / m 2 ;
[0072] Furthermore, the length of the chopped strands of the fiber layer (3) is 3 cm;
[0073] Furthermore, the chopped strands of the fiber layer (3) are evenly spread on the first adhesive layer (2), and the chopped strands are arranged in a disordered manner;
[0074] Furthermore, the fine aggregate used in the recycled fine material layer (4) is fine aggregate obtained by processing RAP old asphalt pavement milling material, and the particle size of the fine aggregate is 0-2.36 mm;
[0075] Furthermore, the old asphalt content of the finely divided aggregate is not less than 13.5%;
[0076] Furthermore, the amount of fine aggregate in the recycled fine material layer (4) is 8 kg / m 2 ;
[0077] Furthermore, the asphalt of the second adhesive layer (5) is a slow-cracking non-stick wheel emulsified asphalt, and the usage amount of the slow-cracking non-stick wheel emulsified asphalt is 0.4 kg / m 2 ;
[0078] Furthermore, the evaporation residue content of the slow-cracking non-stick wheel emulsified asphalt is 50%, the softening point of the evaporation residue is 85°C, and it does not stick to the vehicle tire when the air temperature reaches 60°C;
[0079] Furthermore, the coarse aggregate used in the recycled coarse aggregate layer (6) is finely divided coarse aggregate processed from RAP old asphalt pavement milling material, and the particle size of the finely divided coarse aggregate is 4.75-9.5 mm;
[0080] Furthermore, the old asphalt content of the finely divided coarse aggregate is 0.5%;
[0081] Furthermore, the amount of refined coarse aggregate in the recycled coarse material layer is 64% of the full paving rate.
[0082] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes within the technical scope disclosed by the present invention according to the technical scheme and the utility model concept of the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A crack-resistant synchronous chip seal structure, characterized in that: From bottom to top, it includes the first bonding layer, fiber layer, recycled fine material layer, second bonding layer, and recycled coarse material layer laid on the semi-rigid base layer: The asphalt of the first bonding layer is one of modified emulsified asphalt, polymer modified asphalt and rubber asphalt; The fibers of the fiber layer are one of glass fiber chopped strands and basalt fiber chopped strands; The fine aggregate used in the recycled fine material layer is fine aggregate processed from RAP old asphalt pavement milling material, and the particle size of the fine aggregate is 0-2.36mm; The asphalt of the second bonding layer is slow-cracking non-stick wheel emulsified asphalt; The coarse aggregate used in the recycled coarse material layer is finely divided coarse aggregate processed from RAP old asphalt pavement milling material, and the particle size of the finely divided coarse aggregate is one of 2.36-4.75mm, 4.75-9.5mm, and 9.5-13.2mm.
